The deepest Moho in the Western Carpathians and its respective crustal density model (CEL12 section) - GODOVÁ, Dominika; BIELIK, Miroslav; ŠIMONOVÁ, Barbora (Contributions to Geophysics and Geodesy, 2018)
The main aim of this study is to compile 2-D density model of the CELEBRATION 2000 profile CEL12, which is based on seismic refraction data. The profile CEL12 crosses the External Western Carpathians Flysch zone and is located in the southern part of Poland. The general feature of the resultant density model shows significant changes in the crustal thickness. The Moho depth changes in the interval from 31 km to 43 km. The interpreted 43 km crustal thickness over a 60 km section of the profile results in the discovery of an area, which represents the thickest crust in the entire West Carpathians. This area is situated ∼50 km north-east from the High Tatras in Poland.